The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3758/s13420-018-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Similarity between an unfamiliar human and the owner affects dogs’ preference for human partner when responding to an unsolvable problem

Abstract: This study investigates whether dogs are able to differentiate between people according to whether or not they show similarities to their owners. We hypothesized that dogs would show a preference for the "similar" partner when interacting with unfamiliar humans. After having familiarized with two experimenters displaying different degrees of similarity to their owners, dogs (N = 36) participated in a situation where the desired toy object was made inaccessible in order to find out whether they initiate interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…In line with this, as most dogs were owned by females, it is possible that they generalized Fig. 2 Mean and standard error of the time in seconds that dogs spent gazing at the experimenter during the unsolvable tasks as a function of the experimenter's ID and attitude Table 4 Mean (in bold) and standard deviations (s) of the behaviors assessed their learnt responses with their owner to the female E. This interpretation is in accordance with the results from Kiss et al (2018), which showed that dogs preferred to interact with those experimenters who shared some behavioral attitudes with their owners. Nevertheless, this must be interpreted with caution, as we did not find a direct effect of the owner's gender on dogs' choices.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In line with this, as most dogs were owned by females, it is possible that they generalized Fig. 2 Mean and standard error of the time in seconds that dogs spent gazing at the experimenter during the unsolvable tasks as a function of the experimenter's ID and attitude Table 4 Mean (in bold) and standard deviations (s) of the behaviors assessed their learnt responses with their owner to the female E. This interpretation is in accordance with the results from Kiss et al (2018), which showed that dogs preferred to interact with those experimenters who shared some behavioral attitudes with their owners. Nevertheless, this must be interpreted with caution, as we did not find a direct effect of the owner's gender on dogs' choices.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast to these findings, Kiss, Kovács, Szánthó, and Topál (2018) investigated whether dogs were able to differentiate between unfamiliar people according to their similarity to their owners. To this end, they were confronted with people who either acted as their owner (i.e., behavioral characteristics including language and motion patterns) or wore a similar piece of clothing to one worn by the owner (i.e., unfamiliar arbitrary group marker).…”
mentioning
confidence: 99%
“…This together with the finding that dogs prefer to work with “in-group” humans (c.f. 28 ) might explain their relatively poor pointing-following performance in our study. Importantly, in the present study all subjects participated in four different conditions, thus they completed a relatively large number of experimental trials (e.g.…”
Section: Discussionmentioning
confidence: 61%
“…But our study also revealed that dogs performed more successfully in conditions involving potentially relevant auditory cues (meaningful content with dog-directed intonation) by a socially relevant human companion (the owner). An earlier study by Kiss et al concluded that dogs are more prone to interact in a fetching task upon receiving cues from a person similar to their owners 28 . Moreover, the average latency of response was also found to be the lowest in the owner-involved task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation